Contexts and Repetitions of Cypro-Minoan Inscriptions: Function and Subject Matter of Clay Balls - Ferrara, Silvia (Bulletin of ASOR, 2017)
This article follows the trail of previous suggestions that the so-called clay balls inscribed in the Cypro-Minoan script bear personal names and titles, possibly of high-ranking individuals responsible for industrial and cultic activities at Enkomi, in other Cypriot centers, and at Tiryns on the Greek mainland. We examine attestations of sign-sequences and single signs found on these spherical objects, which occur also in other inscriptions, and cross-check them with the available find contexts of the balls vis-à-vis the structure of their inscriptions. Beyond the likelihood that these objects bear designations of individuals, we suggest that the single signs that often follow a specific sign-sequence on the balls may represent an abbreviated version of the second "word" found on the balls that bear two sequences and no single sign. Furthermore, it is argued that these words in the second position represent a qualifying description of the individual designated by the first sequence. Finally, it is suggested that these objects were possibly used for lot-casting--specifically, for calling individuals to certain tasks.